Vox populi (Dei), vox Dei: Pope Francis’ Theology of the People of God, the Priesthood of All Believers and Democracy - Rudolf von Sinner (Religions)
The Holy See is an absolute monarchy, both as a political and as a spiritual entity. The Second Vatican Council indicated, retrieving biblical terms and metaphors, a new way of giving value to the whole people of God, the laity (laos theou), constituted by baptism. Rather than a societas perfecta in a pyramidal system, the intention was to declericalise and in this sense democratise the church and its decision-making, not least seeking to secure its witness in an ever more secular world. Even if a sacramental and ontological difference is maintained, this indicates clergy are no longer a first class of believers against which the laity would be a second class; rather, they are rooted and stand with and within the whole people of God with their specific vocation and ordination. The notion of the royal and universal priesthood of believers, taken from 1 Peter 2:9 and emphasised by Luther and other reformers as they distributed power between ordained and not ordained leaders, was visible in the Second Vatican Council and finds new enactment in the synodality process which culminated in the Ordinary Synod in Rome, in October 2024. Based on his own theology of the people of God, developed during the dictatorship and economic oppression in Argentina, with strong cultural and religious connotations, Pope Francis seeks to further major involvement of the laity and especially of women in the church’s administration and transformation processes. Not surprisingly, this process has been receiving criticism both from those who find it is not going far enough and from those who believe the process has already gone far too far. Based on bibliographical and documental research, the intention of this article is to describe and analyse the notion of the people of God as proposed by Pope Francis and its forms of concretisation including its deficiencies, as well as, in dialogue with ongoing debates on populism, highlight the precariousness of any “people” as a concept and as a reality. A dynamic notion of “people” and a theological accountability of the people and the clergy towards each other, towards God and towards the world can do justice to both the ambiguities and the irreplaceability of the people as citizens of the church as well as the world.